Gender strategy on weather and climate Information services in East Africa - Nchanji, Eileen Bogweh; Kagabo, Desire; Mvuyibwami, Patrick; Byandaga, Livingstone; Lutomia, Cosmas (2025)
Climate change poses a significant threat to social and economic development in sub-Saharan Africa, particularly in Eastern Africa, where high dependence on agriculture increases vulnerability. However, climate change impacts are not uniform, disproportionately affecting women, youth, and people living with disabilities (PLWDs) due to structural inequalities and limited access to weather and climate information services (WCIS). The Enhancing Climate Change Resilience in East Africa (ECREA) project, funded by the UK Government’s Foreign, Commonwealth and Development Office (FCDO) and implemented by the International Centre for Tropical Agriculture (CIAT) through the Pan-Africa Bean Research Alliance (PABRA), seeks to strengthen the adaptive capacity of smallholder farmers in Kenya, Uganda, Rwanda, and Tanzania. The project focuses on the co-design and co-production of inclusive WCIS and impact-based early warning systems (IBEWS) to improve accessibility and utilization among marginalized groups.